The Camorra and protection rackets: the cost to business. Issue 1 (2nd January 2016) - Frazzica, Giovanni; Lisciandra, Maurizio; Punzo, Valentina; Scaglione, Attilio
Abstract : Based on the observations from the judicial and investigative evidence provided by prosecutors in Camorra areas in Italy, this investigation provides an estimate of the economic impact of extortion racket to businesses. In particular, the estimates refer to the total and average withdrawal of monetary amounts from the businesses victimised by Camorra clans. Further insights are provided in terms of economic activities mostly victimised, and specifically the construction sector, which is subject to a different type of extortion racket.